2002
DOI: 10.1038/sj.bdj.4801369
|View full text |Cite
|
Sign up to set email alerts
|

A randomised crossover trial of post-operative cognitive and psychomotor recovery from benzodiazepine sedation: effects of reversal with flumazenil over a prolonged recovery period

Abstract: 335 RESEARCHA randomised crossover trial of post-operative cognitive and psychomotor recovery from benzodiazepine sedation: effects of reversal with flumazenil over a prolonged recovery period Objective: To study the post-operative cognitive and psychomotor recovery from midazolam conscious sedation, after reversal with the benzodiazepine antagonist flumazenil over a prolonged recovery period. Design: A prospective, double-blind, randomised, crossover trial. Setting: Out-patient Sedation Department, Newcastle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…1,3,6,[8][9][10][12][13][14][15][16][17] Multiple investigators have reported transient cognitive impairment after administration of midazolam in different clinical settings, including gastrointestinal endoscopy, 1,12,13,17 pediatric anesthesia, 6,14-16 and outpatient OMS. 3,10,11 However, most of these studies used various psychomotor assessments as their primary outcome measurement and did not specifically assess recovery room LOS, as was performed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3,6,[8][9][10][12][13][14][15][16][17] Multiple investigators have reported transient cognitive impairment after administration of midazolam in different clinical settings, including gastrointestinal endoscopy, 1,12,13,17 pediatric anesthesia, 6,14-16 and outpatient OMS. 3,10,11 However, most of these studies used various psychomotor assessments as their primary outcome measurement and did not specifically assess recovery room LOS, as was performed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Transient postoperative cognitive impairment caused by midazolam has been well described in the literature and this remains a relevant concern in any ambulatory care setting. 6,8,9 Recently, some evidence has suggested that IV midazolam might be associated with prolonged recovery time when administered for outpatient anesthesia for various oral surgical procedures. 10,11 In addition, unpublished data from the Department of Anesthesiology at the Mayo Clinic (Rochester, MN) have identified midazolam administration as an independent risk factor for prolonged stay in the postanesthesia care unit after general anesthesia for different surgical procedures, including OMS.…”
mentioning
confidence: 99%
“…Nevertheless, flumazenil was not administered because the sedative action of midazolam subsided spontaneously [23].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in ambulatory care settings where post-discharge 'street-fitness' becomes relevant, further concern attaches to the potential adverse effects of midazolam upon cognitive function. However, whilst the adverse effects of midazolam upon adult functioning are well established [4,5], relatively little is known of its effects upon children's cognition.…”
mentioning
confidence: 99%